Cloud characterization from interpolation of SEVIRI imagery - Salgueiro, Vanda (2015)
A methodology to obtain cloud quantities from SEVIRI imager data is described. The methodology is based in the simultaneous interpolation of the measured reflectances and radiances in three spectral channels VIS0.6, IR3.9 and IR10.8, in a domain constituted by the same simulated quantities. This methodology is applied to an area that comprises the Iberian Peninsula. The quantities obtained are the cloud optical thickness (COT), effective radius (reff) and cloud top height (CTH), here presented for the 9 April 2013 at 13:12 UTC. A comparison between the retrieved COT and reff and the corresponding quantities obtained from MODIS cloud product, in a grid of 0.1°x0.1°, is also presented. The comparison shows that these retrieved COT and reff are slightly underestimated.